IOT Bracelets for Guiding Blind People in an Indoor Environment - Ahmad Abusukhon (Journal of Communications Software and Systems, 2023)
Every day, we engage in a variety of activities such as shopping, reading, swimming, and so on. Many people in our community, however, are unable to participate in such activities, due to a variety of eye problems. Directing a blind person to the optimal position (the center of a spot where there is enough space in all directions such that a blind person avoids various obstacles) is a challenge. This paper proposes wireless bracelets that are able to guide a blind person to the optimal position. The proposed system employs ultrasonic sensors in order to detect various obstacles in an indoor environment. It also makes use of the Firebase database and NodeMCU WiFi module to enable real-time communication with a blind individual. Furthermore, the suggested system includes a novel fall-detection mechanism. The proposed Internet of Things (IoT) system is evaluated in an indoor environment. Experiment results showed that the proposed system could efficiently direct a blind person to the optimal position. In comparison to the current state of the art, the proposed system is simpler, less expensive, and more efficient in determining the optimal position to which a blind person must navigate.